Lung regeneration using amniotic fluid mesenchymal stem cells. (3rd April 2018) - Azargoon, Alireza; Negahdari, Babak
Abstract: Respiratory diseases, such as chronic obstructive pulmonary disease (COPD), pulmonary hypertension and lung fibrosis, are yet a major challenge in the world and they result in irreversible structural lung damage. Lung transplantation as the only therapeutic option face some major challenges like graft rejection and cancer, arising as a result of immunosuppression. A low survival rate faced by lung transplantation patients is presently limited to approximately 5 years. Lungs shortage therefore calls for a mechanism that would increase the availability of suitable organs for transplantation. In this review, we give an update on the use of amniotic fluid mesenchymal stem cells (AFMSCs) as an optimal source for lungs scaffold re-cellularization, due to their limitless accessibility and possibility for proliferation and differentiation. Further studies will be required in tissue engineering (TE) and regenerative medicine (RM), especially shifting our focus towards AFMSCs as a cell source for this regeneration.